Electrical/electrochemical impedance for rapid detection of foodborne pathogenic bacteria - Yang, Liju; Bashir, Rashid (Biotechnology advances, 2008)
The realization of rapid, sensitive, and specific methods to detect foodborne pathogenic bacteria is central to implementing effective practice to ensure food safety and security. As a principle of transduction, the impedance technique has been applied in the field of microbiology as a means to detect and/or quantify foodborne pathogenic bacteria. The integration of impedance with biological recognition technology for detection of bacteria has led to the development of impedance biosensors that are finding wide-spread use in the recent years. This paper reviews the progress and applications of impedance microbiology for foodborne pathogenic bacteria detection, particularly the new aspects that have been added to this subject in the past few years, including the use of interdigitated microelectrodes, the development of chip-based impedance microbiology, and the use of equivalent circuits for analysis of the impedance systems. This paper also reviews the significant developments of impedance biosensors for bacteria detection in the past 5 years, focusing on microfabricated microelectrodes-based and microfluidic-based Faradaic electrochemical impedance biosensors, non-Faradaic impedance biosensors, and the integration of impedance biosensors with other techniques such as dielectrophoresis and electropermeabilization.